Information trade : how big tech conquers countries, challenges our rights, and transforms our world - Wichowski, Alexis (New York Harper Collins, 2020)
"In this eye-opening, must-read book, a political insider and tech expert explains what's at stake for our tech-enabled lives-and what we can do about it. Neither an industry apologist nor irrational fearmonger, Alexis Wichowski considers the unchecked rise of tech giants like Facebook, Google, Amazon, Apple, Microsoft, and Tesla-what she calls "net states"-and their growing and unavoidable influence in our lives. Combining original reporting, extensive research, and interviews with technology and government insiders, including Microsoft president Brad Smith, Google CEO Eric Schmidt, and the world's first ambassador to Silicon Valley, Alexis Wichowski explores what happens when we cede our power to tech giants, willingly trading our personal freedom and individual autonomy for an easy, plugged-in existence. Written for the tech-savvy and tech-phobic alike, The Information Trade lays out how net states are conquering countries, challenging our rights, and transforming our future. Most importantly, it shows what we can do to control our relationship with net states before they irreversibly alter how we are governed, how we think, how we act, and how we live"--
Includes bibliographical references.
Keywords: Information services industry; Internet industry; Freedom of information